Induction of p21-Dependent Senescence by an NAE Inhibitor, MLN4924, as a Mechanism of Growth Suppression - Lijun Jia; Hua Li; Yi Sun (Neoplasia: An International Journal for Oncology Research, 2011)
Cullin-RING ubiquitin ligase (CRL), with its founding member of SKP1-Cullins-F-box proteins (SCF) E3 ubiquitin ligase, is the largest family of E3 ligases, which requires cullin neddylation for its activation. Recently, an inhibitor of NEDD8 activating enzyme (NAE), MLN4924, was reported to block cullin neddylation and inactivate CRL/SCF E3, resulting in apoptosis induction and tumor suppression both in vitro and in vivo. We report here that apoptosis is not the sole mechanism by which MLN4924 suppresses tumor cell growth because apoptosis is moderately induced by the drug in some cancer cell lines and drug-induced growth suppression is only partially blocked by a pan-caspase inhibitor, z-VAD. MLN4924 treatment induces the characteristics of senescence phenotypes as evidenced by enlarged and flattened cellular morphology and positive staining of senescence-associated β-Gal. MLN4924-induced senescence is associated with cellular response to DNA damage, triggered by accumulation of DNA-licensing proteins CDT1 and ORC1, as a result of inactivation of CRL/SCF E3s. The senescence occurs in the manner independent of pRB/p16 and p53, but dependent on p21, a known substrate of CRL/SCF E3s and a mediator of senescence, which accumulates on CRL/SCF inactivation by MLN4924. Furthermore, MLN4924-induced senescence is irreversible and coupled with persistent accumulation of p21 and sustained activation of DNA damage response. Our study reveals a novel mechanism of MLN4924 action and showed that MLN4924 could be further developed as an effective anticancer agent by inducing apoptosis and irreversible senescence.